SITUASI DIGLOSIA PADA PENUTUR KABUPATEN BOJONEGORO DAN MADURA DI JAWA TIMUR - Maulidia Dwi Cahyani; Resdianto Permata Raharjo; Titik Indarti (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
The concept of diglosia is first interpreted as a "situation" in which there is a variety of T (high) languages called formal situations and R (low) informal situations. In this concept it has developed and includes a situation in which there are two or more languages that have been distinguished in position. The phenomenon of this research data is the situation of dilosia in men from Java who are married to women from Madura, so that they have children with the initials F who have a variety of different languages in two situations, namely formal and informal. In this study, the author used a qualitative approach with a descriptive method. Data collection techniques are taken using observation. The instrument in this study is to provide question questions, and test / questionnaire questions. Based on the results and discussion, it can be concluded that the child with the initials F has a phenomenon of three languages that differ in position in the situation of diglosia. Keywords: abstract, italic, maximum three words.